POWER RELATION OF THE MAIN CHARACTERS(ANALYSIS OF THE LAST SAMURAI MOVIE SCRIPT) - Yudhi Rahmadi, - (2011)
THE RESEARCH ENTITLED "POWER RELATION OF THE MAIN CHARACTERS (ANALYSIS OF THE LAST SAMURAI MOVIE SCRIPT)" AIMS TO INVESTIGATE HOW THE MAIN CHARACTERS EXERCISE THEIR POWER TO OTHER CHARACTERS AND WHAT TYPES OF POWER THE MAIN CHARACTERS EXERCISE AS EVIDENCED IN THE MOVIE SCRIPT. THE RESEARCH IS QUALITATIVE RESEARCH WITH TEXTUAL ANALYSIS APPROACH. IT EMPLOYS POWER THEORY PROPOSED BY FRENCH AND RAVEN TO ANALYZE THE DATA IN FORM OF WORDS, PHRASES AND SENTENCES TAKEN AS TEXTUAL EVIDENCES FROM THE MOVIE SCRIPT THE LAST SAMURAI. THE RESULT OF ANALYSIS SHOWS THAT THE MAIN CHARACTERS CAN USE OR MANIPULATE DIFFERENT TYPES OF POWER TO ACHIEVE THEIR GOALS. THEY EXERCISE THEIR POWER THROUGH ABSOLUTE POWER OR POSITION, THROUGH A COMPULSION OR THREAT, THROUGH RECOMPENSE FOR WORTHY ACTS AND THROUGH SKILL OR BEING SKILLFUL. THE EXERCISING OF POWER MAKE THESE CHARACTERS GET ANYTHING EASIER. THE RESEARCH ONLY DISCOVERED FOUR TYPES OF POWER EXERCISED BY THE CHARACTERS; COERCIVE POWER, LEGITIMATE POWER, EXPERT POWER AND REWARD POWER.